Análise experimental dos processos de transferência de calor aplicados à concentração solar - Anjos, Vitor Luiz Rigoti dos (2008)
Having in mind the necessity to pump heavy crude oil from notoriously sunny regions of Brazil (northern Brazil regions general speaking or northern Espirito Santo state specifically), the utilization of solar radiation appears as an alternative thermal source to heat on-shore pipelines and storage tanks. The present work exhibits the basic steps to project, design, construction and test of a parabolic solar concentrator prototype, as well as shows experimental results gotten from the activities developed by the whole project and points out some possibilities to enhance the system for future operations. Here, the main objective is to increase heat transfer to a tube installed on parabolic focus (absorber tube). Using distinct configurations for the absorbers tubes, the work fluid is heated and analysis are prosecuted over collected data aiming to reach the main goal, which is to study the pressure drop reduction by viscosity decreasing of heavy oils flow using solar energy collected by a parabolic concentrator.